A xenogeneic‐free bioreactor system for the clinical‐scale expansion of human mesenchymal stem/stromal cells. Issue 6 (4th February 2014) - dos Santos, Francisco; Campbell, Andrew; Fernandes‐Platzgummer, Ana; Andrade, Pedro Z.; Gimble, Jeffrey M.; Wen, Yuan; Boucher, Shayne; Vemuri, Mohan C.; da Silva, Cláudia L.; Cabral, Joaquim M.S.
ABSTRACT The large cell doses (>1 × 106 cells/kg) used in clinical trials with mesenchymal stem/stromal cells (MSC) will require an efficient production process. Moreover, monitoring and control of MSC ex‐vivo expansion is critical to provide a safe and reliable cell product. Bioprocess engineering approaches, such as bioreactor technology, offer the adequate tools to develop and optimize a cost‐effective culture system for the rapid expansion of human MSC for cellular therapy. Herein, a xenogeneic (xeno)‐free microcarrier‐based culture system was successfully established for bone marrow (BM) MSC and adipose tissue‐derived stem/stromal cell (ASC) cultivation using a 1L‐scale controlled stirred‐tank bioreactor, allowing the production of (1.1 ± 0.1) × 108 and (4.5 ± 0.2) × 107 cells for BM MSC and ASC, respectively, after 7 days. Additionally, the effect of different percent air saturation values (%Airsat) and feeding regime on the proliferation and metabolism of BM MSC was evaluated. No significant differences in cell growth and metabolic patterns were observed under 20% and 9%Airsat. Also, the three different feeding regimes studied—(i) 25% daily medium renewal, (ii) 25% medium renewal every 2 days, and (iii) fed‐batch addition of concentrated nutrients and growth factors every 2 days—yielded similar cell numbers, and only slight metabolic differences were observed. Moreover, the immunophenotype (positive for CD73, CD90 and CD105 and negative for CD31, CD80 and HLA‐DR) and multilineage differentiative potential of expanded cells were not affected upon bioreactor culture. These results demonstrated the feasibility of expanding human MSC from different sources in a clinically relevant expansion configuration in a controlled microcarrier‐based stirred culture system under xeno‐free conditions. The further optimization of this bioreactor culture system will represent a crucial step towards an efficient GMP‐compliant clinical‐scale MSC production system. Biotechnol. Bioeng. 2014;111: 1116–1127. © 2014 Wiley Periodicals, Inc.